Explicitation sequences in conversation: some considerations on formulations, candidate inferences and grounding - Chernyshova, Elizaveta (My University, 2018)
This conversation analysis study focuses on sequences where speakers make a piece of information explicit (explicitation sequences). Among others, formulations (Heritage & Watson 1979) and candidate inferences (turns submitting an inference and requiring a confirmation in a second position) can initiate an explicitation. Based on a short analysis of conversational data in French this study shows that, despite their similarities, formulations and candidate inferences have different impacts on the grounding processes in conversation (Clark & Brennan 1991). More generally, this paper is concerned with the questions of inference and information in the co-construction of meaning in interaction.